Forest biogeochemistry in response to drought. (18th November 2015) - Schlesinger, William H.; Dietze, Michael C.; Jackson, Robert B.; Phillips, Richard P.; Rhoades, Charles C.; Rustad, Lindsey E.; Vose, James M.
Abstract: Trees alter their use and allocation of nutrients in response to drought, and changes in soil nutrient cycling and trace gas flux (N2 O and CH4 ) are observed when experimental drought is imposed on forests. In extreme droughts, trees are increasingly susceptible to attack by pests and pathogens, which can lead to major changes in nutrient flux to the soil. Extreme droughts often lead to more common and more intense forest fires, causing dramatic changes in the nutrient storage and loss from forest ecosystems. Changes in the future manifestation of drought will affect carbon uptake and storage in forests, leading to feedbacks to the Earth's climate system. We must improve the recognition of drought in nature, our ability to manage our forests in the face of drought, and the parameterization of drought in earth system models for improved predictions of carbon uptake and storage in the world's forests.